Water Wells’ Rehabilitation: A Case Study of Northern Part of Ekiti East Local Government Area, Southwestern Nigeria - Popoola, K.; Talabi, A. O.; Ojo, A. A. (European Journal of Applied Sciences, 2022)
Potable water is scarce during dry season (October to March) each year in the northern part of Ekiti East Local Government Area, southwestern Nigeria. Rain harvested water serves as alternative source of water during the rainy season. Other forms of surface water are often contaminated by open defecation apart from being expensive to treat and circulate to points of needs. The area of study lacks pipe borne water and a good number of boreholes in the area had lost their original yield while some had completely broken down due to mineral sediments, screen incrustation, silt fill-up bottom sump, submersible pump coil damage, impeller wear, faulty grouting and cementation. In order to have access to potable groundwater, rehabilitation was carried out on abandoned water wells which were earlier drilled through government intervention being fairly cheaper than constructing new boreholes. Rehabilitation of these wells was done by removing the submersible pump, flushing and back washing with pressured water, air lifting, grout reconstruction and cementation, which restored the yield of these water wells to their original yield. The results had shown that the borehole rehabilitation in northern part of Ekiti East Local Government Area will provide sustainable water borehole yield but to avoid well yield shortage, borehole in this area must be flushed with compressed air or high pressure water at the end of raining season every year because of thick overburden peculiarity of boreholes in the study area which comprise of Ilasa, Ikun/Araromi, Ishaya, Kota, part of Omuo-Oke and Omuo-Ekiti.